Espanhol e português: os pronomes pessoais sujeito em produções escritas em língua não materna - Rosa, Jéssica Rodrigues (2019)
In this dissertation we seek to understand how the clause subject is filled in by the subject personal pronoun (PPS) in written productions, in Brazilian Portuguese (PB) by Spanish speakers and in Spanish (E) by Brazilians. In order to understand written productions in a foreign language, it is important a bibliographical research on the clause subject in the two languages involved. Duarte (1995) shows that PB is increasingly dissociating from the characteristics of a pro-drop language and, consequently, from European Portuguese (PE) when presenting a high PPS index. On the other hand, in Soriano’s (1999) description, the “syntactic behavior” of Spanish resembles the PE. González (1994), who studied Brazilian students’ productions, called this difference “inverse asymmetry” between PB and PE in relation to the use of tonic and atonic pronouns. The main objective of this research is to verify if there is any similarity in the use of PPS in the written production of the apprentices of these two languages when they are learning the other as a foreign language. We have started from the initial hypothesis, based on Almeida Filho (2004), that learners of Portuguese as a foreign language (PLE) and Spanish as a foreign language (ELE) adopt similar strategies. For the gathering, we proposed to the research participants to develop to write two texts. The results of this master’s research, however, we cannot compare equally the strategy of the two groups because the participants were acting in different contexts: those of ELE were in the context of non-immersion, while those of PLE were in Brazil at the time of the data collection.